Chemotherapy in the Prevention of Recurrence of Echinococcosis of the Liver - Rakhmanov Kosim Erdanovich; Makhramkulov Zafar Mamirkulovich; Makhmudov Saidinjon Botrzonovich; Abdurakhmanov Diyor Shukurillaevich (Zien Journals, 2022)
The aim of the study is to improve the quality of treatment of patients with echinococcosis of the liver by developing effective methods to reduce the recurrence of the disease
Keywords: echinococcosis; chemotherapy; relapse; prevention